MEANING ANALYSIS AND DYNAMIC EQUIVALENCE - Abdullaeva Ismigul; Azimjon Ahmedov (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation. The study aimed to test the effectiveness of “dynamic equivalence” and “contextual correspondence” theories in two translation contexts. The study found that applying the theories of “dynamic equivalence” and “contextual correspondence” in translating scientific articles and technical terms proved effective in achieving meaning-based translations. Furthermore, it affirmed that cultural translation contributes to a higher level of comprehension among target readers/listeners.